Peran Kepala Sekolah Dalam Implementasi Manajemen Mutu Peserta Didik (SMK Darul Maghfiroh Di Sinar Rejeki, Kecamatan Jati Agung, Kabupaten Lampung Selatan) - Andrianto (STAI Terpadu Yogyakarta, 2020)
The role of the principal in implementing the quality management of learners is the activity of the principal responsible for the implementation of education, the school principal must be able to manage the management process from the planning, implementation, and to the evaluation stage of the outcome of learning, to achieve the success of the organization or institutions in achieving objectives and various objectives and ability to face various challenges, both external and , practices in the field, this can affect the performance of teachers in carrying out their duties in teaching and learners who receive the lesson, so that it can achieve the quality of education. The type of research used is field research, i.e. research that includes the facts and problems that exist in the field, with the method of research used is the descriptive qualitative research in SMK Darul Maghfiroh SInar Rejeki, District Jati Agung, Kabupaten Lampung Selatan, with the technique of collecting data in this research include: observation, interviews, documentation, while the validity test of data is done with the triangulation technique, during the research is analysts , data presentation, and withdrawal of conclusions. The role of the principal in the implementation of quality management by carrying out its duties precisely is planning, organizing activities, directing activities, implementing supervision, and implementing management management and organizing the school relationship with the community and other Instasi. The principal is the control holder in his school so that in organizing and implementing it all the headmaster can not do it alone, the principal should be able to invite and give a positive influence so that teachers and students can cooperate wholeheartedly, with such a purpose the school will be easier to achieve.